Akseptabilitas dan Kapabilitas Kepala Desa Perempuan dalam Pemerintahan Desa - Bestari, Afdhalia Nurfitri (Program Studi Ilmu Politik Fakultas Ilmu Sosial Universitas Negeri Semarang, 2018)
Culture the patriarch who developed in Indonesia where people his boy more the power to lead and the people of his boy is more dominant than of women. This raised stereotype where the people thought that her no weak can think rational and viewed number two. To there was discrimination women in political domain. Women are not feasible and capable of as the leader. Because it was necessary the study on leadership women in this research. The result of this research suggests that acceptability the existence of a female superior already accepted by the community. The social reality of a female superior specifically in the Mindaka described through three moment dialectical from Peter Berger, namely existence, objectivity, and internalization. Capabilities of village women in leading the village derived from experience organize owned and style village head leadership Mindaka focused attention to the transaction interpersonal between leader with the exchange election involves interaction with the community organizations.